ANALYSIS OF TUBE BUNDLE HEAT TRANSFER TO VERTICAL FOAM FLOW - Gylys, J.; Sinkunas, S.; Zdankus, T. (Revista de Engenharia Térmica, 2005)
Phenomena of foam flow and associated heat transfer are rather complex. Foam is a twophase flow, which structure changes while it passes an obstacle: bubbles divide into smaller bubbles and liquid drains down from flow. Due to these peculiarities, an application of analytical methods for their study is a complex subject. Thus experimental method of investigation was selected in our work. The investigation apparatus consisted of foam generator, vertical channel and staggered bank of horizontal tubes. The cross section of the channel had square profile with side dimension 140 mm. Tubes in the bank were located in three vertical rows with five tubes in each of them. Experiments were performed within Reynolds number diapason for gas from 190 to 450 and foam void volumetric fraction from 0.996 to 0.998. Direction of foam motion in vertical channels also influences heat transfer intensity. Investigations of heat transfer process of upward and downward moving statically stable foam flow from horizontal tube bank were performed. Experimental heat transfer results of tube bundle in vertical cross foam flow were summarized by criterion equations, which enable determination of heat transfer intensity of the entire bundle or of a separate tube of the bundle for different values of void volumetric fractions and regime parameters of statically stable foam flow.